Neologisms in Kostan Zaryan’s Collection of Works – “The Crown of the Days” - GRIGORYAN, SUSANNA (Bulletin of Yerevan University B: Philology, 2021)
The vocabulary of Kostan Zaryan’s poems is rich and multiform. The poet has made use of the whole rich lexical material of our language masterly and in case of need, he also used the word-building possibilities of the Armenian language, creating new words and expressions and in this way enriching not only the language of his own works but also the boundaries of the literary language. More than 300 author neologisms are included in Kostan Zaryan’s collection of works- “The Crown of the Days” which are not reflected in any of the dictionaries of neologisms of the Armenian language. Those poetically formed neologisms which are created according to the principle of the complex of ready-made patterns give additional shades of meaning to the speech of the author, have stylistic value and contribute to the greater expressiveness of speech. The compound words created by Kostan Zaryan are made by means of quite different words. The prefixal-suffixal (derivational) neologisms, which are mainly melodious and are formed according to the rules and regulations of word-formation tradition, are not numerous in Kostan Zaryan’s poems.